Berthe Morisot - Higonnet, Anne, 1959- (University of California Press, 1995)
Of the six Impressionist painters whose first exhibition scandalized and fascinated Paris in 1874, Berthe Morisot was the only woman. She reached a pinnacle of artistic achievement despite the restraints society placed on her sex, adroitly combining her artistic ambitions with a rewarding family life. Anne Higonnet brings fully to life an accomplished artist and her world.